The Impact of Different Flap Designs on Periodontal Outcomes in Alveoalar Bone Cleft Surgery for Orthodontic Patients. A Randomized Control Trial - Marij Hameed, Abid Kanju, Nousheen Khan, Syeda Midhat Batool, Taimur Khan, Samar Nazir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Alveolar bone grafting (ABG) is a critical surgical intervention in patients with a cleft of the alveolus, aimed at reconstructing the alveolar ridge to facilitate proper eruption, periodontal support, and alignment of adjacent permanent teeth. Objective: The aim of this study is to determine the impact of different flap designs on periodontal outcomes in alveolar bone cleft surgery for orthodontic patients. Methods: This research comprised 86 individuals who underwent M3 extraction for either acute or chronic periodontal issues and pericoronitis. Patiets were divided in two groups. Group I received envelope flap and group II received triangular flap. Outcomes were examined in terms of gingival recession (REC) reported at six locations and pain score Results: In group I mean age was 35.47±20.62 years and in group II mean age was 36.51±14.74 years. 26 cases in group I and 27 in group II were males. In group I 10 (23.3%) cases had history of smoking and in group II 8 (18.6%) cases had history. There were statistical difference was observed between both groups in terms of pain score and gingival recession (REC). Conclusion: We concluded that envelope flap presented better outcomes as compared to triangular flap in terms of wound healing, gingival recession and pain score. Keywords: Bone cleft, PPD, CAL, Flap Designs